2009
DOI: 10.7205/milmed-d-03-7608
|View full text |Cite
|
Sign up to set email alerts
|

Prepatellar Septic Bursitis: A Case Report of Skin Necrosis Associated With Open Bursectomy

Abstract: Patients with prepatellar septic bursitis are typically successfully managed nonoperatively with rest, compression, immobilization, aspiration, and antibiotics. Rarely, surgical excision of the bursa may be required for recalcitrant cases. Prepatellar bursectomy, however, has been associated with considerable risk of surgical-site morbidity. Although skin necrosis is frequently cited as a complication of open bursectomy, there is limited information in the medical literature on the etiology and management of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Gendernalik et al [3] reported a case of skin necrosis associated with open bursectomy and the application of a continuous vacuum dressing. Failure to appreciate the tenuous blood supply to the overlying skin can result wound dehiscence and sinus formation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gendernalik et al [3] reported a case of skin necrosis associated with open bursectomy and the application of a continuous vacuum dressing. Failure to appreciate the tenuous blood supply to the overlying skin can result wound dehiscence and sinus formation.…”
Section: Discussionmentioning
confidence: 98%
“…Prompt treatment with the appropriate antibiotics often avoids the need for surgical debridement. There are a number of potential complications in performing open debridement in this setting such as wound breakdown and skin necrosis, which is not only a significant morbidity for the patient but also requires a prolonged hospital admission with multiple surgeries [3]. The successful non-operative management with intravenous antibiotics alone has been reported but the average hospital admission for this cohort of patients was 11 days [4].…”
Section: Introductionmentioning
confidence: 98%
“…Prepatellar septic bursitis is usually successfully managed non-operatively with rest, compression, immobilisation, aspiration and antibiotics. Surgical bursectomy may rarely be required for recalcitrant cases [6] .…”
Section: Septic Bursitismentioning
confidence: 99%
“…Recurrence rates have been reported as high as 20%. Complications of the open approach include wound haematoma, scar tenderness, damage to the infrapatellar branch of the saphenous nerve, seroma formation, and skin necrosis [5][6][7]. Endoscopic procedures are performed through multiple portals and can be effective in terms of postoperative recovery and cosmesis.…”
Section: Introductionmentioning
confidence: 99%